2005
DOI: 10.1196/annals.1327.094
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Midgut Stem Cell Proliferation and Differentiation by Insect Hormones and Peptides

Abstract: Stem cells derived from midguts of the caterpillar, Spodoptera littoralis, can be induced to multiply and differentiate in vitro. Ecdysone (E) and 20-hydroxyecdysone (20E) had a concentration-dependent effect: E was more active in cell proliferation and 20E in differentiation. Ecdysteroid receptors in midgut stem cell nuclei were stained with the antibody 9B9. In addition, alpha-arylphorin and four midgut differentiation factors (MDF) specifically stimulated proliferation and differentiation of stem cells, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 9 publications
2
25
0
Order By: Relevance
“…20,21 An arylphorin subunit, acting as a monomer, has been shown to stimulate cell proliferation and differentiation in several species of moth both in vitro and in vivo. [22][23][24] In the wax moth, the haemolytic and cytotoxic effects of hemolymph have been attributed to a typical hexameric arylphorin, which may thus contribute to the insect's immune response. 25,26 The impressive accumulation of storage proteins just before metamorphosis is readily observed when they are associated with coloured ligands such as the blue bilins that originate from heme cleavage.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 An arylphorin subunit, acting as a monomer, has been shown to stimulate cell proliferation and differentiation in several species of moth both in vitro and in vivo. [22][23][24] In the wax moth, the haemolytic and cytotoxic effects of hemolymph have been attributed to a typical hexameric arylphorin, which may thus contribute to the insect's immune response. 25,26 The impressive accumulation of storage proteins just before metamorphosis is readily observed when they are associated with coloured ligands such as the blue bilins that originate from heme cleavage.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, stem cells multiply in the presence of low titers of steroid hormones E (Smagghe et al, 2005) or 20E (Sadrud-Din et al, 1994) in the absence of juvenile hormone (Parthasarathy and Palli, 2008), mimicking the hormonal balance that exists prior to a molt (Riddiford, 1994). We have shown that at least two peptidic factors control stem cell multiplication: the fast-acting and quickly exhausted brain peptide bombyxin and the slower-acting, longer-lasting blood and fat body peptide, a-arylphorin (Blackburn et al, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…However, Smagghe et al (2005) showed that ecdysone (E) as well as 20E could serve as a midgut stem cell proliferation agent, although effectiveness was concentration-dependent (Smagghe et al, 2005). 20E was effective only in the absence of juvenile hormone (JH) in stimulating midgut stem cell proliferation in beetle midgut (Tribolium castaneum) in vitro (Parthasarathy Cell-free extracts of fat body (FBX) from pupae of M. sexta and H. virescens were prepared and assayed for effects on highly enriched preparations of stem cells obtained from cultured midgut (Loeb et al, 1999).…”
Section: Ecdysonesmentioning
confidence: 99%
“…In the past decade, signi fi cant progress has been made in the preparation of primary cultures of midgut insect stem cells (reviewed by Hakim et al 2010 ) . Midgut epithelial cell cultures from lepidopterans and coleopterans have been established and maintained in vitro for periods up to 3-6 months while preserving their differentiated characteristics (Sadrud-Din et al 1996 ;Smagghe et al 2005b ) . These primary midgut cell cultures have been applied for the study of Bt endotoxin binding to the microvilli of intact epithelial cells from different lepidopteran species (Wang and McCarthy 1997 ;Loeb et al 2001 ) .…”
Section: Insect Cell Lines For the Evaluation And Screening Of Bt Insmentioning
confidence: 99%